2019
DOI: 10.1002/jqs.3137
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of human physical and behavioural evolution during the last 1 million years

Abstract: This paper reviews some of the main advances in our understanding of human evolution over the last 1 million years, presenting a holistic overview of a field defined by interdisciplinary approaches to studying the origins of our species. We begin by briefly summarizing the climatic context across the Old World for the last 1 million years before directly addressing the fossil and archaeological records. The main themes in this work explore (i) recent discoveries in the fossil record over the last 15 years, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 311 publications
2
54
0
Order By: Relevance
“…One of those adaptive strategies could have been short-term migration, either vertically to the nearby more humid higher elevated grounds (Foerster et al, 2015;Ossendorf et al, 2019) or longitudinally and latitudinally to lake or river refugia that were not affected by the dry spells. Both would have contributed to a periodic cultural and genetic exchange, which is thought to be one of the key drivers in cultural innovation and, on longer time scales, evolution (Lahr and Foley, 1998;Scerri et al, 2018;Galway-Witham et al, 2019), with innovations being generally favored by the exchange of cultural information (Ackermann et al, 2016).…”
Section: Implications For Human Adaptationsmentioning
confidence: 99%
“…One of those adaptive strategies could have been short-term migration, either vertically to the nearby more humid higher elevated grounds (Foerster et al, 2015;Ossendorf et al, 2019) or longitudinally and latitudinally to lake or river refugia that were not affected by the dry spells. Both would have contributed to a periodic cultural and genetic exchange, which is thought to be one of the key drivers in cultural innovation and, on longer time scales, evolution (Lahr and Foley, 1998;Scerri et al, 2018;Galway-Witham et al, 2019), with innovations being generally favored by the exchange of cultural information (Ackermann et al, 2016).…”
Section: Implications For Human Adaptationsmentioning
confidence: 99%
“…Finally, it is suggested that there was an interplay between technological development and cultural behavior and physiology. These were possibly self-reinforcing, since these developments could help secure the energy needs of a larger brain and a larger brain could also lead to more diversity in and capacity for cultural and technological development (Sterelny, 2010;Antón and Snodgrass, 2012;Galway-Witham et al, 2019). Indeed, there is evidence that modern behavior stabilized 150,000 years ago, around the time that the parietal lobe also reached its current dimensions (Schlebusch et al, 2017;Bruner, 2018;Neubauer et al, 2018;Davies, 2019).…”
Section: Storage Of Information and History Of Human Development: Arcmentioning
confidence: 99%
“…This period, especially from data gathered in the European and Middle Eastern archeological records, has been called the “Upper Paleolithic.” Some have even argued that, because of this unique development, behaviorally “modern” humans emerged during this period ( Klein, 2009 ). However, this classification has been questioned in the literature, especially considering newer archeological findings in Africa ( McBrearty and Brooks, 2000 ; Galway-Witham et al, 2019 ). The “explosion” of artifacts may indeed be due to a more highly concentrated population and other factors ( Galway-Witham et al, 2019 ).…”
Section: Contemporary Advances In Science Of Memory Cognitive Sciencmentioning
confidence: 99%
See 1 more Smart Citation
“…Our knowledge about the origins of symbolically mediated behaviors has substantially increased over the last twenty years. The idea of a symbolic explosion occurring in Europe 40,000 years ago [1][2][3], associated with the arrival of anatomically modern human populations in the region, has given way to a complex gradualist scenario [4][5][6][7]. Multiple evidence now demonstrates that behaviors generally associated with symbolic thought, such as producing abstract drawings and engravings, using pigments, wearing personal ornaments and performing complex mortuary practices, are three to ten times older than what was acknowledged two decades ago.…”
Section: Introductionmentioning
confidence: 99%